2005
DOI: 10.1523/jneurosci.3553-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

A GIT1/PIX/Rac/PAK Signaling Module Regulates Spine Morphogenesis and Synapse Formation through MLC

Abstract: Three of seven recently identified genes mutated in nonsyndromic mental retardation are involved in Rho family signaling. Two of the gene products, ␣-p-21-activated kinase (PAK) interacting exchange factor (␣PIX) and PAK3, form a complex with the synaptic adaptor protein G-protein-coupled receptor kinase-interacting protein 1 (GIT1). Using an RNA interference approach, we show that GIT1 is critical for spine and synapse formation. We also show that Rac is locally activated in dendritic spines using fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
337
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(367 citation statements)
references
References 30 publications
25
337
2
Order By: Relevance
“…GIT1 was shown to target ßPix to the synapse, where it locally activates Rac1 and PAK. Importantly, disruption of the synaptic localization of GIT1 or interfering with ßPix function, perturbs spine morphogenesis and synapse formation [91]. Consistent with these findings, the Drosophila homologue, dPIX, has been demonstrated to play a major role in regulating post-synaptic structures and protein localization at the glutamatergic neuromuscular junction [64].…”
Section: Arhgef6mentioning
confidence: 70%
See 1 more Smart Citation
“…GIT1 was shown to target ßPix to the synapse, where it locally activates Rac1 and PAK. Importantly, disruption of the synaptic localization of GIT1 or interfering with ßPix function, perturbs spine morphogenesis and synapse formation [91]. Consistent with these findings, the Drosophila homologue, dPIX, has been demonstrated to play a major role in regulating post-synaptic structures and protein localization at the glutamatergic neuromuscular junction [64].…”
Section: Arhgef6mentioning
confidence: 70%
“…They noticed that these defects were associated with reduced expression of AMPARs at the synapse and LTP [9]. In a parallel study, Zhang et al demonstrated that PAK1 and 3 regulate spine morphogenesis by triggering the phosphorylation of MLC, the latter resulting in an increase in dendritic spine size and synapse formation [91]. More recently, mice lacking the PAK3 gene were generated, and analysis of these mice showed selective impairment in late-phase hippocampal LTP, a distinct form of long-term synaptic plasticity involving new gene expression.…”
Section: Pak3mentioning
confidence: 99%
“…GIT1 has also been shown to modulate synapse formation in hippocampal neurons, through recruitment of the GIT-PIX-PAK complex to dendritic spines and synapses [74]. However, recruitment of GIT1 to spines does not require interaction with paxillin.…”
Section: Gitsmentioning
confidence: 99%
“…There is also strong evidence for a redistribution of polyribosomes from dendritic shafts to active synapses (Ostroff et al, 2002). Activity might thus promote local movement of a number of molecules into spines, and PAK3 might not only be part of these changes but also participate in their regulation, notably through its possible action on proteins, such as cofilin, myosin II regulatory light chain, or cortactin (Edwards et al, 1999;Hashimoto et al, 2001;Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%